Răspuns :
2×y+4×y+...+4028×y=2014×2015
2×y(1+2+...+2014)=2014×2015
2×y×2014×2015/2=2014×2015
y×2014×2015=2014×2015
y=1
2×y(1+2+...+2014)=2014×2015
2×y×2014×2015/2=2014×2015
y×2014×2015=2014×2015
y=1
2×y+4×y+...+4028×y=2014×2015
2×y(1+2+3+..+2014)=2014×2015
2×y×2014×2015:2=2014×2015
y×2014×2015=2014×1015
şi fiindcă avem 2014×2015 si inainte de egal si după egal.....daca mai avem si acel y ,il eliminăm. ..şi rezultatul va fi 1 .
2×y(1+2+3+..+2014)=2014×2015
2×y×2014×2015:2=2014×2015
y×2014×2015=2014×1015
şi fiindcă avem 2014×2015 si inainte de egal si după egal.....daca mai avem si acel y ,il eliminăm. ..şi rezultatul va fi 1 .